Movement Pedagogy: balancing Physical Education classes at different levels of education (Research, Society and Development, 2020)
Currently, one of the biggest challenges in Physical Education remains the theoretical discussion combined with the procedures of practical classes. Thus, the objective of the study was to analyze the possibilities and limitations of the theme “balance yourself”, based on the proposal of Pedagogy of the Movement, at different levels of education, in Physical Education classes. For 0this, the descriptive method of the experience report type was adopted. The same lesson plan proposal was applied in three different classes, namely, Elementary, High School and University (Physical Education Degree). After analyzing the reports, it was possible to identify similarities between the interventions, such as: acceptance of the lesson proposal and feelings of motivation and satisfaction in working in groups. Differences, on the other hand, occurred when students in High School were afraid to touch their classmates and in University, fear and insecurity did not stand out as in other levels of education. Finally, we conclude that there is potential in this pedagogical proposal and we have not identified limitations.